Comparative efficacy of laser and electroacupuncture on anxiety management and salivary alpha-amylase levels in pediatric dental patients with excessive gag reflexes: a randomized clinical trial - Marwa Baraka; Sarah I. Zeitoun; Sara Salah; Sawsan Hafez (BMC Oral Health)
Abstract Background This study examines the effects of laser acupuncture and electroacupuncture on anxiety in children with excessive gag reflexes during dental impressions. Methods A three-armed randomized controlled trial involved 63 pediatric dental patients aged 6–9 with excessive gag reflexes. Participants were equally divided into three groups: group 1 (laser acupuncture), group 2 (electroacupuncture), and group 3 (negative control with a deactivated device). Salivary alpha-amylase (sAA) levels, Frankl scores, facial image scale (FIS), and heart rate were measured before and after interventions to assess dental anxiety. Group comparisons were conducted using one-way ANOVA or Kruskal-Wallis tests, followed by Bonferroni-corrected pairwise comparisons for significant results, with significance defined as p < 0.05. Results The study found no significant differences in sAA levels before the intervention, but electroacupuncture significantly reduced levels post-intervention (p = 0.009) compared to the laser and control groups. Frankl scores also improved significantly with electroacupuncture (p = 0.002), indicating better cooperation during dental procedures. Both electroacupuncture and laser groups reduced heart rates significantly compared to control (p < 0.001), with correlations indicating that higher sAA levels were associated with increased discomfort in the laser group, and that stress levels were linked to heart rate in the control group. Conclusions Both laser acupuncture and electroacupuncture effectively lowered anxiety level in children with gag reflex. While both methods improved objective and subjective scores, electroacupuncture demonstrated superior efficacy in managing anxiety. Clinical relevance These findings support acupuncture techniques as valuable tools in pediatric dentistry for improving patient cooperation and managing anxiety during dental procedures. Trial registration Registered on clinicaltrial.gov; NCT06422286, 16/4/2024.